Analysis of the Similarity of the Macroeconomic Situation and the Level of Investment in the European Union in 2018-2020 in the Context of the Covid-19 - Pukin-Sowul, Paulina; Markowski, Lesław (Olsztyn Economic Journal, 2022)
The purpose of this article was to determine the macroeconomic and investment situation in 2018-2020 in the Member States of the European Union. The work also deals with the division of the European Union into three parts: the core, the periphery, and Central and Eastern Europe. A critical analysis of the scientific literature was used to present the economic consequences of the pandemic. Ward's method was used to create a few clusters of European Union Member States that are most similar to each other in terms of macroeconomic situation and investments. During the pandemic, the macroeconomic and investment situation worsened. Moreover, there are three groups of member states in the European Union, which indicates that there are still significant development and economic disproportions between the groups in the EU.